Journalisme public et gestion des enjeux sociaux - Thierry Watine; Michel Beauchamp (Communication, 2000)
A concept which has been emerging since the end of the 1980s, public journalism may be defined as an approach in which the media play a much more active role in their communities : 1) by offering concrete solutions to problems which affect the daily lives of their citizens ; and 2) by encouraging citizens to be more involved in the democratic process. Here, the authors present a case study of the « Spécial Emploi » campaign organized by Québec City daily newspaper, Le Soleil, in the spring of 1996 in an attempt to verify to what degree — and within what limitations — was this campaign one of public journalism. The authors try to establish links between this new approach, and theoretical streams such as « the social responsibility of media », « the democratic participation of citizens » and « the involvement of business in social issues ».